China and the End of Global Silver, 1873-1937 - Dean, Austin, 1984- (Book collections on Project MUSE., 2020)
"For a very long time, silver was money, but in the late nineteenth century, much of the world adopted some variant of the gold standard. China, however, remained the most populous country still using silver, although the country had no unified national currency; there was not one standard, but many: silver coins circulated alongside chunks of silver and every transaction became an "encounter of wits." This book focuses on how officials, policymakers, bankers, merchants, academics, and journalists in China and around the world answered a simple question: how should China change its monetary system? As different governments in China attempted to create a unified monetary standard in the late 19th and early 20th century, imperial powers--the United States, England, and Japan--tried to shape the direction of Chinese monetary reform for their own benefit. This book argues that the Silver Era in World history ended due to the interaction of imperial competition in East Asia and the state-building projects of different governments in China. When the Nationalist government of China went off the silver standard in 1935, it marked not just a key moment in Chinese history, but in world history"--